The marriage pact [large type] - Fuller, Kathleen (Fuller, Kathleen. Amish of Marigold novels, 2025)
"Perry and Daisy's fake relationship is fooling everyone . . . but they're the ones who might be getting fooled. When Daisy Hershberger and Perry Bontrager meet, they discover they have one thing in common: both their families are way too eager to see them make a good match. Daisy is convinced that Maynard is the one for her, but her parents have their doubts. And Perry? His family wonders if there's anyone out there for a quirky guy like him. He's also certain that some people -- himself included -- are destined to be single for life. After comparing notes, Perry and Daisy agree to a pact. He'll help her make Maynard realize what he's missing, and she'll pretend to be Perry's love interest to keep his matchmaking mother satisfied. For a while, their pact seems to be working. Maybe their imagined futures aren't exactly what fairy tales are made of, but they're committed to their plan . . . until they realize that a real-life fairy tale is happening where they least expect it. Sometimes, you don't have to pretend to be anything but yourself in order for love to find you."--